Social capital and university–business collaboration in doctoral education - Santos, P.; Thune, T. M. (Industry and Higher Education, 2022)
University–business collaboration in doctoral education has been promoted by governments and universities. In contexts where there is limited contact between the academic and business sectors, individuals and their social capital might play an important role in the formation and success of such partnerships, including the frequency of interaction and continuity of partnerships. Here, data from a survey of directors of doctoral programmes in Portugal were used to explore these aspects. The social capital of the directors seems to increase both the intensity and continuity of collaboration, especially in scientific fields considered to be more distant from companies and in which university–business collaboration is less common. Previous collaboration will create relational capital, resulting in mutual knowledge and trust which, in turn, lead to more intense and sustainable collaboration. Academic experience with companies—reflecting cognitive aspects of social capital—increases the diversity of university–business collaboration in doctoral programmes, while also reinforcing the possibility of long-term collaborations. The findings indicate that academics’ social capital is an important factor in determining the success of collaborative doctoral education, and should be taken into account when designing and supporting collaborative doctoral programmes.